Growth Inhibition and Oxidative Stress in Two Green Algal Species Exposed to Erythromycin. (21st April 2021) - Ma, Zhihua; Yang, Fangshe; Ren, Jingya; Fan, Rong; Duan, Qiannan; Guo, Jipu; Guo, Jiahua
Abstract: Chlorella vulgaris ( C. vulgaris ) and Raphidocelis subcapitata ( R. subcapitata ) are two model algal species applied for the testing of chemicals, whereas a considerable variation in their sensitivity to antibiotics has been reported. The difference in species sensitivity may be attributed to the xenobiotic‐induced oxidative stress in algal cells. Thus, this study compared the responses of these two model green algae toward the exposure of erythromycin (ERY), a macrolide antibiotic, at the concentration levels of 0, 20, 40, 60 μg/L, and elucidated the toxic mechanism of action from the point of oxidative damage and antioxidant defense. To achieve this, effects on the endpoints of algal growth, malondialdehyde (MDA), antioxidants (superoxide dismutase [SOD], catalase [CAT], glutathione peroxidase [GP], glutathione, and glutathione S‐transferase), and photosynthetic pigment contents were evaluated. After exposing for seven days, the growth of R. subcapitata was significantly stimulated at ERY 20 μg/L but inhibited at the higher exposure level of 60 μg/L. Contrarily, hormesis in C. vulgaris exposed to all ERY treatments was detected. With the increase in ERY exposure, MDA content, and the antioxidant activity of SOD, CAT, GP in R. subcapitata were gradually enhanced. In C. vulgaris, a declining trend in the MDA content and the activity of SOD, CAT, and GP was detected. These results provide insights into the ERY‐altered production of reactive oxygen species and the antioxidant responses in two algae. Abstract : Research Impact Statement : The production of reactive oxygen species (ROS) and antioxidants may account for the hormesis of growth and different sensitivity in Chlorella vulgaris and Raphidocelis subcapitata to ERY exposure.